Long-Term Fate of the Neoaortic Root After Neonatal Ross Operation: A Case Series. Issue 3 (May 2019) - Pradegan, Nicola; Castaldi, Biagio; Azzolina, Danila; Stellin, Giovanni; Vida, Vladimiro L.
The aim of this study is to analyze the adaptation properties of the pulmonary autograft in four infants who underwent the Ross operation before one year of life. The patients underwent serial echocardiographic assessments of the autograft diameters at short- and long-term follow-up and values were reported as the Z scores for normal aortic and pulmonary diameters. At a median follow-up time of 18.5 years (range: 18.2-19.4 years), all the patients are alive, none requiring autograft reinterventions. This series shows excellent adaptation potential of the "infant pulmonary autograph" in the long-term, during somatic growth of the patient.